Adam Schall von Bell, who advocated for the adoption of Western calendars during the late Ming and early Qing dynasties and suffered unjust imprisonment - WANG Zhiliang, (Journal of Research for Christianity in China (JRCC), 2025)
The lunar calendar still in use in China today is actually the Shixian Calendar promulgated over 300 years ago after the Qing Dynasty established its capital in Beijing. This calendar represents a fusion of Chinese and Western elements, applying Western astronomical theories and computational systems while preserving the structure of China's traditional calendar system. Its revision and promulgation were directly linked to the German missionary Johann Adam Schall von Bell. Arriving in China during the late Ming and early Qing dynasties, Johann Adam Schall von Bell earned imperial favor for his contributions to reforming the Chinese calendar. He rose to become the “Imperial Preacher” seated before the Qing emperor's throne. Yet this very position brought him misfortune, nearly leading to his execution by lingchi.
Keywords: Adam Schall von Bell, Western calendars, late Ming and early Qing